Research on conceptual identification of underground miners’ unsafe behavior in coal mines - Ninghao SUN; Yu GUO; Guoyu DONG; Ruipeng TONG (Meikuang Anquan)
In order to clarify the basic concepts of underground coal miners’ unsafe behavior, a research framework is proposed by combining text mining, rooted theory, and logical thinking. A definition library of 172 descriptions is created by looking through the literature and selecting the pertinent definition descriptions. The definition of unsafe behavior can be logically expressed in terms of the five elements of definition mode, behavior subject, behavior cause, behavior nature and behavior result. From these five elements, many sorts of definitions can be derived, totaling 1215. Eleven typical descriptions are selected for conceptual analysis, the theoretical connotation of underground coal miners’ unsafe behavior is discussed, and a new definition is proposed. The definitions of unsafe behavior of three domestic coal mining enterprises are selected to carry out comparative analysis. The results show that the proposed definition of unsafe behavior of coal mine workers is feasible, and the new definition is scientific and reasonable.